Microplastic stress in plants: effects on plant growth and their remediations - Jia, Li; Liu, Lining; Zhang, Yujing; Fu, Wenxuan; Liu, Xing; Wang, Qianqian; Tanveer, Mohsin; Huang, Liping (Frontiers in Plant Science, 2023)
Microplastics (MPs) pollution is becoming a worldwide dilemma due to their resilience, long-term persistence, and robustness in different ecosystems. In terrestrial ecosystem, plants are being exposed to MPs stress, thereby affecting overall plant growth and development. This review article has critically analyzed the effects of MPs stress in plants. We found that MPs stress induced reduction in plant physical growth is accompanied with two complementary effects, (i) blockage of pores in seed coat or roots to alter water and nutrient uptake, (ii) induction of drought due to increased soil cracking effects of MP. Nonetheless, the reduction in physiological growth under MP stress is accompanied with four complementary effects, (i) excessive production of ROS, (ii) alteration in leaf and root ionome, (iii) impaired hormonal regulation, (iv) decline in chlorophyll and photosynthesis. Given that, we suggested targeting the redox regulatory mechanisms could be beneficial in improving MPs tolerance in plants, however the antioxidants activities are highly plant species-, tissue-, and MPs type- specific and dose dependent. MPs stress also indirectly reduces plant growth by altering soil productivity. However, MPs induced negative affects vary due to the presence of different surface functional groups and particle size. At the end, we suggested the utilization of agronomic approaches, including application of growth regulators, biochar, and replacing plastic mulch with crop residues, crop diversification and biological degradation, to ameliorate the effects of MP stress in plants. The efficiency of these methods are also MPs- type specific, and dose dependent.